Pengaruh Lokasi, Kelengkapan Produk, dan Pelayanan Terhadap Keputusan Pembelian Konsumen pada Imam Market Kisaran - Elly Rahayu (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
This study is purpose to examine the influence of location, completeness of products and services to consumer purchasing decisions at Swalayan Imam Market. The population of this study are consumers who have been shopping at Imam Market Kisaran. The sample of this study is the consumers who shop at Imam Market within the last 3 months The technique sampling used is accidental sampling method . Best of the t test (partial test) that have been done, Service dan Location which have influence to consumer buying decition on Imam Market Kisaran and product completeness has no effect to consumer buying decision on Imam Market Kisaran Keywords: Location, Product Completeness, Purchasing Decision Service, Consumer